2010
DOI: 10.1063/1.3483463
|View full text |Cite
|
Sign up to set email alerts
|

New study of the stability and of the spectroscopy of the molecular anions NCO− and CNO−

Abstract: Using highly correlated wave functions, the ground and the low lying excited states of the molecular NCO(-) and CNO(-) anions have been reinvestigated. The stability of the electronic ground state of the two isomers with respect to dissociation and to electron detachment has been checked along the isomerization pathway. The regions of stability of the excited electronic states have been analyzed and identified and it is shown that only the ground state is stable and the corresponding potential energy surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
5
15
0
Order By: Relevance
“…All the present values agree well with those reported by Leonard et al 20 The computed trend of geometric changes with the basis set expansions is reported by Table 4.…”
Section: The Ab Initio Structural Energiessupporting
confidence: 92%
See 1 more Smart Citation
“…All the present values agree well with those reported by Leonard et al 20 The computed trend of geometric changes with the basis set expansions is reported by Table 4.…”
Section: The Ab Initio Structural Energiessupporting
confidence: 92%
“…The product NCO at its equilibrium geometry was also obtained with the same level of calculations as reported in that table. All values are in very good accord with recent calculations on the same system, 20 so we can consider the above parameters to be quite accurate in describing the reacting species.…”
Section: The Ab Initio Structural Energiessupporting
confidence: 87%
“… [a] Calculated values from ref. 16: 1.193 Å for NC and 1.229 Å for CO bond. [b] Calculated values from ref.…”
Section: Resultsmentioning
confidence: 99%
“…[b] Calculated for the [Re(XCO)(CO) 2 (triphos Me )] compounds. [c] Previous computations give 2166 and 1228 cm −1 for $\tilde \nu $ asym and $\tilde \nu $ sym , respectively 16. [d] Previous computations at the CCSD(T) level give 1803.7 and 786.2 cm −1 for $\tilde \nu $ asym and $\tilde \nu $ sym , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note here that from the calculated PEC of C 2 H − from reference [15] we found 21 bound levels along the additional bond between C − 2 and the hydrogen atom, while our present calculations generate a potential energy curve which supports 24 vibrational levels, as expected from the increase in the well depth and the stronger tail of the long-range part of the PEC. If we turn now to the interaction in the NCO − anion, we note that the full potential energy curves for its lowest-lying electron state X 1 Σ + and for the next higher electronic excited states have been already presented elsewhere [19], where it was shown that the ground state of NCO − is stable with respect to electron detachment processes and it is also energetically well separated from the excited electronic states of both anion and neutral radical species. The one dimensional cut for the collinear arrangement of the pseudo-2Body potential for the lowest electronic ground state PEC of NCO − , when considering only the newly formed bond with the incoming oxygen atom,is given in is the dipolar polarization coefficient of the hydrogen atom [22].…”
Section: Introductionmentioning
confidence: 84%